Floor slab construction / Ahmad Aiman Wafiq Zainan - Wafiq Zainan, Ahmad Aiman (2021)
Floor slab is an important structure that bears load from above. Hence, this report will discuss in detail about the construction of a floor slab. This report is produced based on the concrete floor slab structure at a multipurpose hall in Bagan Datuk, Perak. The objective of this report is to investigate the method statement of floor slab installation. From this, we can understand the details of a floor slab thoroughly. This is also to solve the occurring problems associated to construction stage. It is to demonstrate the construction of floor slab via its structure, process of installation and post-installation. This report will provide a proper guide in improving a floor slab after several outcomes in different point of perspective so that the impact could be brought through innovation and technology.